2015
DOI: 10.1007/s11046-015-9902-5
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Refractory Majocchi’s Granuloma with Voriconazole and Review of Published Literature

Abstract: Majocchi's granuloma (MG) is a rare deep skin dermatophyte infection that can occur either in immunocompetent or in immunocompromised individuals. Oral itraconazole or terbinafine is considered to be the first choice of treatment. We report an immunocompetent man with deep nodular form of MG, the form which is generally found in immunosuppressed individuals. Previous treatment with either oral itraconazole or terbinafine yielded no apparent improvement. After a series of examination, the man was diagnosed as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Although ketoconazole was frequently used previously, about half of the patients reported today are treated with terbinafine (250 mg/day). 8 , 13 , 36 , 40 , 43 , 47 , 54 , 68 71 Other systemic antifungal drugs are itraconazole (100–200 mg/day), 32 , 44 , 53 , 72 griseofulvin (250–500 mg/day), 10 , 35 , 63 voriconazole, 73 and posaconazole. 28 Antifungal therapy should be continued until the lesions are completely resolved.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ketoconazole was frequently used previously, about half of the patients reported today are treated with terbinafine (250 mg/day). 8 , 13 , 36 , 40 , 43 , 47 , 54 , 68 71 Other systemic antifungal drugs are itraconazole (100–200 mg/day), 32 , 44 , 53 , 72 griseofulvin (250–500 mg/day), 10 , 35 , 63 voriconazole, 73 and posaconazole. 28 Antifungal therapy should be continued until the lesions are completely resolved.…”
Section: Treatmentmentioning
confidence: 99%
“…Rallis et al 37 reported a patient who did not respond to systemic itraconazole treatment, but responded well to systemic terbinafine treatment. Liu et al 73 reported the case of a patient with a mixed infection of T . rubrum and Klebsiella pneumoniae and treated this case first with systemic antibiotics (combined cefoselis and levofloxacin for 7 days) and then voriconazole (200 mg, twice daily).…”
Section: Treatmentmentioning
confidence: 99%
“…However, in a recently published case, an immunocompetent man with an MG refractory to itraconazole and oral terbinafine was treated successfully with voriconazole [7]. …”
Section: Discussionmentioning
confidence: 99%
“…The higher efficacy of voriconazole might be related to the broader spectrum of activity against various fungal pathogens, the rapid absorption after oral administration, the high bioavailability (90%-96%) with steady plasma concentration after oral intake, the absence of affection by gastric PH and the efficient distribution to the different human tissues. 4,10 The challenge in our case was the past history of liver transplantation; such patients are vulnerable to different type of infections due to the immunocompromised status that lead to unusual presentations and…”
Section: Case Reportmentioning
confidence: 99%